Estágio supervisionado e aprendizagens da docência - Magalhães, Elisa Gomes (2009)
This study was a qualitative investigation result on the Curricular Supervised Training (CST) and its importance on the constitution of bias in learning and teaching process through the formative course lived by pupils of the sixth term of the Pedagogy Course in Federal University of São Carlos. The questioning that orientated this research was: Which Supervised Curricular Training contributions to teacher initial education in the vision of future general education teachers, pupils of a Pedagogy Course? The general objective sought the description and analysis of aspects regarding the learning and teaching process in elapsing of CST, in a more specific way: the relationships among the experiences of the degree course and the supervised training; the possibilities and the limitations of training in the learning of abilities, attitudes and teacher's knowledge; relevant aspects of teacher initial education highlighted starting from the CST, the expectations, difficulties, dilemmas, challenges and conflicts lived during the CST, their ways of coping and analysis, finally, the impressions and conceptions, noticed in the CST about teacher action in the classroom and his future action as professor in this context . Thus, the theoretical referencial of this research was constituted through readings and reflections accomplished during the study delineation, searching to evidence teacher initial education accomplishing a brief historical survey, and also a short discussion over social changes that we have been living and how they influence teacher education. In that sense, it also brought a discussion about the training, a brief historical contextualization; and its role on teacher education. The data collection was accomplished by means of a characterization of subject’s questionnaire, field diaries, report and an interview with the teacher’s future. In this sense, the data were analyzed in light of taught theory, and reflects CST contributions in the learning of teaching aspects. Finally, it was possible to notice that the training, according to the future teachers, contributed in a relevant way for them to visualize teacher action and his future action in the school context, as well as learning peculiar characteristics of teaching. CST can be structured in a better way and can supply better conditions to make that future teachers notice and understand the function which they have being formed.